A study of the tectonically active Marmara region, Turkey, using a global positioning system (GPS) - Dogan, U; Lachapelle, G; Fortes, L; Ergintav, S (NATL RESEARCH COUNCIL CANADA, 2003)
The Marmara region is an active tectonic zone characterized by a transition in the dextral strike-slip regime of the western part of the North Anatolian Fault Zone. The main goal of this paper is to assess the use of global positioning system (GPS) data sets collected during five relatively short time intervals during the period December 2000 - March 2002 to detect potential crustal deformations. To determine if the deformations measured with GPS are real or only a data artifact, a statistical reliability analysis of the solutions is performed. The results indicate that each station has statistically different temporal behavior and significant relative motions. This area is consequently still very active, with significant deformation patterns. Although the average magnitude for our estimated displacement rates with respect to ANKR station, which represents the rigid motion of the Anatolian plate, is in the order of 1.1 cm/year in the south of the North Anatolian Fault, it increases to 2.3 cm/year in the northern part of the area.
Keywords: 12 NOVEMBER 1999; EARTHQUAKE; RELIABILITY; DEFORMATION; KINEMATICS; DUZCE; IZMIT; Geology